MONITORING AIR QUALITY SYSTEM BASED ON SMART DEVICE INTELLIGENT - Beni Satria; Hermansyah Alam; Rahmaniar Rahmaniar (Jurnal Ekonomi, 2023)
Life on Earth can no longer be free from pollution. Pollution has an unfavorable impact, especially for health. Air pollution, for example, besides being able to trigger lung health problems, can also increase the risk of glaucoma which can result in blindness. Air pollution is pollution in the air by the presence of various contaminants beyond the threshold. A journal published by LAPAN said that some of these pollutants have the chemical elements CO, NO, SO, SPM (suspended particulate matter, O) and various heavy metals such as lead. Globally, the contributors to air pollution come from the transportation sector. In this study a design was designed. a system that can monitor air quality in a place, using the MQ-135 sensor, which is a gas sensor that has a relatively high sensitivity to ammonia, benzene, alcohol, CO2, smoke and other gases. And the MQ-7 sensor is a gas sensor used in equipment to detect carbon monoxide (CO) gas in everyday life, industry or cars. This system is based on the ATMega8 microcontroller as the main processor, and monitoring results are displayed on a 2 x 16 character LCD. So that the system becomes portable but still reliable to use. flat shape which makes it easy to lift up and causes losses to increase.